Effects of fishing practice changes on pelagic shark longline captures in the Gulf of Gabes, Tunisia. Issue 1 (24th November 2019) - Saidi, Bechir; Karaa, Sami; Enajjar, Samira; Bradaï, Mohamed. N.
Abstract: In order to increase their catches, longliners targeting sharks in the Gulf of Gabes, Tunisia, have increased the number of hooks per basket and have included new bait types instead of mackerel ( Scomber scombrus ). This paper reports the effects of these changes on catch composition, catch rates, size distribution, life‐stage captures, and mortality at haulback. Data from 48 and 96 longline sets, carried out during the shark fishing seasons of 2007 and 2008, with two hooks per basket, and 2016 and 2017, with five hooks per basket, respectively, were examined to assess the effect of gear change. Moreover, the effects of bait types were inspected based on 33 fishing sets using whole mackerel, 19 using salema ( Sarpa salpa ) halves, and 27 using pieces of stingray ( Dasyatis  spp.), sampled during 2016 and 2017. The species composition indicated that longliners expand the vertical distribution of their hooks to operate from the surface to the bottom. The catches with both longline designs were dominated by sandbar shark ( Carcharhinus plumbeus ). Despite gear changes, the catch rate of C. plumbeus decreased by 42.21%, suggesting population decline. The size composition indicated a shift towards larger specimens, mainly adult females, which could jeopardize the shark population. Moreover, the mortality of the main species at haulback seems to be affected by the design of the longline. The bait used, mainly pieces of stingray, significantly increased the catch rate of sandbar shark, which suggests a greater attractiveness of the new bait; however, fish size and mortality rates at haulback were unchanged in response to bait variation. The fishery operates in shark nursery grounds, which exposes these fish (principally C. plumbeus ) to considerable exploitation pressure. The new fishing practices intensified the pressure and thus the risk of a rapid depletion of populations. To preserve the shark species in the area, the use of new gear and attractive bait should be banned.